Mediating Effect of Job Experience on the Relation Between Level of Education and Moral Integrity at the Workplace (Journal of Education and Educational Development, 2023)
Education plays a crucial role in the individual’s critical thinking, knowledge, behavior, values, morals, and integrity and is considered an essential qualification in the workplace. On the other hand, moral integrity is to do the right thing and not to be involved in dishonest practices for personal or further gains, even when not being monitored. he presents study investigated the impact of the level of education on individuals’ moral integrity and, later, its reflection in the workplace. This study also investigated the mediation effect of job experience on this relationship. Differences in moral integrity between males and females were further analyzed to compare. For data collection, three hundred and fifty-three executives from different industries were approached through convenience sampling. Data was then analyzed through SPSS 24.0 using inferential statistics. The findings showed that the educational level of employees impacts moral integrity, and the mediating effect of job experience was found significant. Moreover, no gender difference could be found, concluding that moral integrity was equally essential for employees of both genders. The study revealed the aspects that can contribute to the moral integrity of individuals, and education seemed to be the most important one. The study further strengthened the HR department to improve their hiring, placement policies and policymakers to invest in education more to combat corruption and keep moral integrity high among employees. It will also help the originations consider individuals’ educational levels before hiring. Furthermore, the present study emphasized the inclusion of moral education from the very beginning, so individuals can understand the importance of morals and moral integrity.